The Coyote-Scholar in the Doctoral Theatre and Performance Studies Classroom: Reading Rabinal Achí, Güegüence, sor Juana, and Rascón Banda - Graham-Jones, Jean (Latin American Theatre Review, 2017)
In this essay, I describe two seminars I have created for students in a US doctoral theatre studies program. In both seminars, we study Latin American theatre and performance of distinct periods as well as considering these texts and practices from different conceptual places. In this approach, I have sought to put into pedagogical practice the various strategies and potential I attribute to Delia Poey’s concept of the coyote-scholar. Noting that we scholars, much like the border-crossing coyote, participate in transporting marginalized texts into academic discourse, Poey urges us to engage with the perturbing, disrupting, and recontextualizing potential of coyote-scholarship. In describing the initial class meetings of “The Borders of Latino American Theatre and Performance” and “Transatlantic Theatre and Performance: Golden Age Spain and Pre-Conquest-Colonial Latin America,” as well as collective class projects and the experience of conducting one of the seminars at Chile’s Pontificia Universidad Católica, I trace my students’ growing engagements as coyote-scholars and artists.